Prospects of the Use of Mobile-Assisted Language Learning (MALL) Applications in Public Speaking Courses - Alonto, Anifa (FKIP - Universitas Tanjungpura, 2024)
This study explores the effectiveness of mobile-assisted language learning applications in enhancing the speaking skills of university students enrolled in a public speaking course. Two applications were employed to target fluency and pronunciation. Peer evaluation assessed fluency using one application, while informal teacher evaluation focused on pronunciation with another. Students provided feedback on the functionality of both applications. Results indicated that participants found the applications helpful, expressing a positive reception to incorporating such technology to supplement their course learning.